SILICATE BRICK BASED ON LIME-BELITE BINDER SYSTEMS AND DUNE SANDS - Naurizbaev Azamat; Ilyasov Allanazar; Qayratdinova Aynura; Nurymbetov Baxtiyar; Toremuratov Sharibay (Journals Park Publishing, 2022)
The possibility of improving the physicochemical and physico-mechanical properties of silicate materials obtained based on lime-belite binder systems and dune sands, for the first time was revealed in the article. Regulation of the hydration processes of structure-formation of lime-belite binder systems with local mineral microfillers under normal and hydrothermal conditions and the dosages of fillers were determined; the mechanisms of their action were explained.